Antimicrobial and Antiinflammatory Studies on Some 1,2,4-Triazolo[3,4-b][1,3,4]thiadiazines and 1,2,4- Triazolo[3,4-b][1,3,4]thiadiazoles Containing Quinoxaline - WAGLE, SHIVANANDA; VASUDEVA ADHIKARI, AIRODY; SUCHETHA KUMARI, NALILU (Asian Journal of Chemistry, 2010)
The reaction of 2-(3-methyl-2-oxo quinoxalin-1(2H)-yl) acetohydrazide (1), with carbon disulphide in presence of methanolic potassium hydroxide at 0 ºC affords potassium dithiocarbazate (2), which on treatment with 70 % hydrazine hydrate at 100 ºC undergoes smooth cyclization to give 1-[(4-amino-5-mercapto-4H-1,2,4-triazol-3- yl)methyl]-3-methyl quinoxalin-2(1H)-one (3), in good yield. This triazole has been conveniently converted into title compounds, 3-methyl-1-[(6-phenyl-7H-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazin-3-yl) methyl]quinoxalin-2(1H)-one (4a-j), by condensing it with phenacyl bromides in ethanol at reflux temperature. In another reaction, the triazole 3 has been treated with aromatic carboxylic acids in presence of phosphorus oxychloride at 100 ºC to afford title compounds, 3-methyl-1-[(6-phenyl[1,2,4]triazolo[3,4-b][1,3,4]thiadiazol-3-yl)- methyl]quinoxalin-2(1H)-one (5a-j). The prepared compounds have been characterized by IR, 1H NMR, 13C NMR and mass spectral data, followed by elemental analysis. These compounds were screened for their in vitro antibacterial activity against five pathogenic strains and antifungal activity against four fungi. Further, selected compounds were subjected to in vivo antiinflammatory activity. Few of them exhibited promising activity.